Answers

2015-10-21T14:46:15+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Since the lines are passing through the origin then (0,0) will be the points of both ,

equation of first line

y - 0 = 3(x-0)

y = 3x ----(1)

equation of second line ,

y = -2x -----(2)

combining(1) & (2 We get (y+2x)(2y-x) = 0)
We get 6x² - y² + xy = 0
1 5 1
Sorry , I don't knw wht happened , i m posting here (y-3x)(y+2x) = 0 , 6x² - y² + xy = 0 , is the answer
2015-10-21T15:32:51+05:30
Equation of a line passing through origin(0,0) with slope 3 i
(y-0) = 3(x-0)
⇒ y = 3x 
⇒ y - 3x = 0 ---------(1)

equation of a line passing through origin(0,0) with slope -2 is
(y-0) = -2(x-0)
⇒ y = -2x 
⇒ y + 2x = 0 ---------(2)

Combining lines (1) and (2), we get
(y - 3x)(y + 2x) = 0
⇒ y² + (2x-3x)y - 6x² = 0
⇒ y² - 6x² -xy = 0
⇒ 6x² - y² + xy = 0

Equation of combination of lines is 6x² - y² + xy = 0
0
thnx for telling , i was confused ^_^